Prevalence of Bacterial Infection in Lungs of Slaughtered Goats in North Eastern Uttar Pradesh - Jaiswal1, Sandeep K.; Niyog, Debasish; Tripathi, Krishna K.; Shrivastav, Dharam P.; Gupta, Rakesh K.; Yadav, Vibha; Singh, Satyavrat (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Goats are among the main meat-producing animals in India. Many bacteria, viruses, parasites and allergic reactions are contributorsof pneumonia in goats. Pneumonia is a serious threat to either individual or flocks, resulting in poor live weight gain. In the presentstudy 180 cases of goats slaughtered in the local market of Gorakhpur and Maharajganj districts of Uttar Pradesh were included. 63lung samples exhibiting gross lesions of pneumonia were screened for bacteriological and histopathological changes. Identificationof the organisms was done based on cultural, morphological and biochemical characteristics. Among the tested 63 lung samples, total14 (22.22%), 08 (12.69) and 05 (07.93%) were found to be suggestive of Escherichia coli, Staphylococcus and Klebsiella spp., respectively.Necropsy revealed that 35% (63/180) of the slaughtered goats were infected with the lung lesions, and 42.87 % (27/63) of the lunglesions were due to the bacterial agents or organisms.
Keywords: Bacterial isolates; Biochemical tests; Goat; Lungs; Pneumonia; Slaughter